HUKUM BISNIS TERHADAP PERDAGANGAN INTERNASIONAL ERA GLOBALISASI SEBAGAI PERLINDUNGAN EKSPORTIR, IMPORTIR, DAN INVESTOR - Prijanto, Tulus; Tho’in, Muhammad (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2021)
The purpose of this study is to determine legal protection for international trade in the era of globalization and digital as a form of legal certainty for business people, especially international businesses. This type of research is a qualitative descriptive study. The method in research uses the literature study method with a normative juridical approach supported by a variety of relevant library materials, especially journals. The results show that the legal principles that are carried out in international business transactions (trade) which are global in nature can be found in the legal principles of international agreements, the rule of law that regulates various kinds of provisions and procedures for implementing transactions. The provisions are concerning Contracts for the international Sale of Goods and the UNIDROIT Principle of International Contracts (1994). Legal certainty given to international business actors in business engagements based on the legal source of the international business engagement itself.